Addition of the Electronic Educational Material to Doctor’s Face-to-Face Education Has No Additive Effects on Hypertension Control: A Randomized Single Blind Study - John Yang Lee; Dihua Tang; Xinhua Xiao; Xiaoping Liang; Huihon Piao; Mian Xie (International Journal of Hypertension, 2020)
Background. Patient education is effective for HTN treatment. There are many methods of patient education improving HTN control. Are there additive effects of combination of different educational methods for HTN treatment? Objective. To assess the effects of addition of the electronic educational material to doctor’s face-to-face education for HTN control. Method. We designed a randomized single blind study to compare the doctor’s face-to-face education alone and its combination with the electronic educational material over the cell phone. Participants were patients with a confirmed diagnosis of primary HTN. Electronic educational material over the cell phone was the intervention. Main measures were standard blood pressure measurements before and after 12 weeks of treatment. Result. The baseline characteristics of the intervention and control groups including the age, sex, SBP, DBP, and HTN control rate were not significantly different. After 12 weeks of follow-up, the blood pressure and the HTN control rate seemed worse in the combination group; however, the differences between the intervention group and the control group were not statistically significant. Conclusion. There were no additive effects in the combination of the doctor’s face-to-face education and the electronic educational material over the cell phone.